Synthesis and properties of metal matrix composite foams based on austenitic stainless steels -titanium carbonitrides - Bakan, Halil I.; Korkmaz, Kemal (Elsevier Sci Ltd, 2015)
Metal matrix composite foams based on 316L stainless steel and reinforced with TiC0.7N0.3 were produced by the replication method using polyurethane sponge as a template. The rheological properties of the slurry appeared to be the key issue in the preparation of the composite foams. A homogeneous distribution of TiC0.7N0.3 particles throughout the 316L matrix and a good interaction between the 316L matrix and TiC0.7N0.3 reinforcement particles were obtained. Compression strength results showed that TiC0.7N0.3 particles acted as the real reinforcement medium. The values of the compressive yield strength and the elastic modulus of the metal matrix composite foams increased significantly with increasing TiC0.7N0.3 content when compared to the open cell 316L stainless steel foams. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Metal-matrix composites (MMCs); Foams; Powder processing; Sintering